On Quasi rgα-open and Quasi rgα -closed Functions In Topological Spaces (Journal of the College of Basic Education, 2022)
In this paper, we introduce and study new types of open and closed functions called ( quasi rgα-open functions ) and ( quasi rgα –closed functions ) . Also, we study the Characterizations and basic properties of quasi rgα-open functions and quasi rgα-closed functions .